Pengaruh Literasi Keuangan, Inklusi Keuangan, Sumber Daya Manusia dan Dukungan Pemerintah Terhadap Kinerja Usaha Mikro Kecil dan Menengah Kabupaten Gresik - Safitri, Lia Nur; Chamalinda, Khy'sh Nusri Leapatra (Unversitas Islam Madura, 2024)
The existence of MSMEs plays an important role in the Indonesian economy. This research focuses on testing and providing empirical evidence regarding the influence of financial literacy, financial inclusion, human resources and government support on the performance of MSMEs in Gresik Regency. This type of research uses quantitative methods. Primary data was obtained from a questionnaire which was measured using a Likert scale and secondary data was obtained from MSME data in Gresik Regency. This research used a purposive sampling technique and sampling using the Slovin formula to obtain 394 respondents from the food and beverage sector. The analysis tool uses the SPSS test and t test to test the hypothesis in this research. The results of this research show that the performance of MSMEs in Gresik Regency is influenced positively and significantly by the variables of financial literacy, financial inclusion, human resources and government support.